If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 3) + (x + 2) + (x + 7) = 40 Reorder the terms: x + (3 + x) + (x + 2) + (x + 7) = 40 Remove parenthesis around (3 + x) x + 3 + x + (x + 2) + (x + 7) = 40 Reorder the terms: x + 3 + x + (2 + x) + (x + 7) = 40 Remove parenthesis around (2 + x) x + 3 + x + 2 + x + (x + 7) = 40 Reorder the terms: x + 3 + x + 2 + x + (7 + x) = 40 Remove parenthesis around (7 + x) x + 3 + x + 2 + x + 7 + x = 40 Reorder the terms: 3 + 2 + 7 + x + x + x + x = 40 Combine like terms: 3 + 2 = 5 5 + 7 + x + x + x + x = 40 Combine like terms: 5 + 7 = 12 12 + x + x + x + x = 40 Combine like terms: x + x = 2x 12 + 2x + x + x = 40 Combine like terms: 2x + x = 3x 12 + 3x + x = 40 Combine like terms: 3x + x = 4x 12 + 4x = 40 Solving 12 + 4x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 4x = 40 + -12 Combine like terms: 12 + -12 = 0 0 + 4x = 40 + -12 4x = 40 + -12 Combine like terms: 40 + -12 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| 3y^4+16y^2+5=0 | | 2(5x-11)=14 | | 8h=6h-13 | | 87=-6x+5+x | | 9lnx=-1 | | -8(8k-7)=-456 | | (2b+9)/11=8 | | 4x-11=(2x-5)(x-3) | | -5(-10a+2)=390 | | x/3+14=29 | | 12/5=(3+z)/z | | 3x^-3/(2y)^-2 | | y^2-12y+32= | | 32+14-3= | | x-2/x+7=x-6/3x+21 | | 16-3m=-11 | | 2(1+7p)+9=151 | | 32+14-x= | | 3x-9=22 | | 8+5x=56 | | (2y+5)-(y-3)+(7y-3y)=17 | | m/-3.2=15 | | -2(1-9r)=-182 | | 13x+7x-10+10=180 | | 4-5/432-5 | | A=a+2b+4c | | 50m=600 | | 6x^2-27x+27= | | cos(2x)=1 | | 0=6x^2+3x-9 | | x^2-10x+4= | | y=.04*0 |